The effectiveness of the individual approach in physical rehabilitation of men with metabolic syndrome to improve atherogenic lipid profile - Єльнікова, Марина (Slobozhanskyi Herald of Science and Sport, 2016)
Marina Elnikova Purpose: evaluation of the effectiveness of individual approach in physical rehabilitation of men with metabolic syndrome based on the dynamics of indicators of the atherogenic lipid profile. Material & Methods: theoretical analysis and compilation of scientific and methodical literature and internet providers; biochemical methods; methods of mathematical statistics. To study involved 60 men with metabolic syndrome. Results: application of individual approach in the long-term form of rehabilitant-rehabilitation interaction at the outpatient rehabilitation stage of men with the metabolic syndrome improves lipid profile, significantly reduces total cholesterol, low-density lipoprotein, triglycerides and increases high-density lipoprotein.